Black Hole-Galaxy Scaling Relation Evolution From z~2.5: Simulated Observations With HARMONI on the ELT - García-Lorenzo, Begoña; Monreal-Ibero, Ana; Mediavilla, Evencio; Pereira-Santaella, Miguel; Thatte, Niranjan (Frontiers in Astronomy and Space Sciences, 2019)
We present preliminary results on the potential of HARMONI, the first light integral field spectrograph for the ELT, to explore the evolution of central super massive black holes (SMBH) - host galaxy relation in the range from z∼0.7 to z∼2.5. We simulated HARMONI observations of QSO+host galaxy at different redshifts, assuming different morphologies for the host galaxy. As input, we combined MUSE observations of nearby galaxies and a theoretical QSO spectrum. These were dimmed and redshifted to the desired cosmic epoch. We scaled the total host galaxy luminosity to three different values, sampling three orders of magnitude. Likewise, we assumed two different luminosities for the central QSO. Simulations were performed for the 30×60 mas2 HARMONI spatial scale and LTAO working at 0.67 arcsec seeing. The selected wavelength range (i.e. 4700-5300 A ̊ at rest-frame) was sampled at the lowest HARMONI spectral resolving power (i.e. R∼3200). This configuration included all the ingredients to estimate the host galaxy parameters and the SMBH mass, as well as for assessing the morphological type of the host galaxy.